Comparative Evaluation of Antimicrobial Activities of Different Types of Luting Cements - Sazan Sherdl Saleem (Erbil Dental Journal)
Background and objectives: To minimize secondary caries, luting cements with antimicrobial properties are frequently used for the cementation of indirect restorations. The aim of this study was to investigate the antimicrobial effect of four dental luting cements